2020
DOI: 10.1186/s12886-020-01593-9
|View full text |Cite
|
Sign up to set email alerts
|

VEGF, apelin and HO-1 in diabetic patients with retinopathy: a correlation analysis

Abstract: Background: It's necessary to analyze the role of VEGF, apelin, and HO-1 in patients with type 2 diabetes (T2DM), and to evaluate its relevance to diabetic retinopathy (DR). Methods: T2DM patients who were treated in our hospital from December 1, 2018 to November 30, 2019 were included. T2DM patients were divided into non-DR (NDR) group, non-proliferative DR (NPDR) group, and proliferative DR (PDR) group. and healthy participants were selected as the control group. The value of VEGF, apelin, and HO1 in predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In this study, VEGF decreased, indicating that the combined use of glimepiride and recombinant human insulin injection can reduce blood sugar and inhibit the inhibition of VEGF in the liver. ere is an abnormally high expression of a variety of factors within the tumor, which thereby reduces the occurrence of tumor cells [21]. e effective rate of treatment in the study group was significantly higher than that in the control group (P < 0.05).…”
Section: Discussionmentioning
confidence: 85%
“…In this study, VEGF decreased, indicating that the combined use of glimepiride and recombinant human insulin injection can reduce blood sugar and inhibit the inhibition of VEGF in the liver. ere is an abnormally high expression of a variety of factors within the tumor, which thereby reduces the occurrence of tumor cells [21]. e effective rate of treatment in the study group was significantly higher than that in the control group (P < 0.05).…”
Section: Discussionmentioning
confidence: 85%
“…The LL genotype and the L allele of the (GT)n repeat polymorphisms in the HO-1 gene were risk factors for VFL development, and HO-1 concentrations were decreased in cases compared to controls ( 16 ), which indicates a lower production of anti-inflammatory and anti-oxidative substances, increasing the likelihood of developing diseases. The (GT)n repeat polymorphisms in HO-1 have been associated with severe acute pancreatitis ( 49 ), encephalitis in HIV infection ( 50 ), pediatric non-alcoholic fatty liver disease ( 51 ), and cancer ( 52 ), and lower levels of HO-1 are linked to diabetic retinopathy ( 53 ) and peripheral artery diseases ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, apelin is confirmed as a potent angiogenic factor, especially in retinal endothelium. It is reported that the serum apelin-13 level has a positive correlation with proliferative diabetic retinopathy, which is unrelated with VEGF (93) (94,95). Li Yang et al found that apelin can induce the proliferation, migration, and expression of the cytoskeleton and tight junction protein through the PI3K/Akt and MAPK/ERK pathways in human retinal pigment epithelial cells (96).…”
Section: Vascular Effects Endothelial Dysfunction and Angiogenesismentioning
confidence: 99%